1993
DOI: 10.1095/biolreprod49.5.1083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deoxyribonucleic Acid Protamination on Fluorochrome Staining and in Situ Nick-Translation of Murine and Human Mature Spermatozoa1

Abstract: A major event in enhancing sperm chromatin stability is the replacement of the histones by protamines during spermiogenesis. In this study, we present results indicating that chromomycin A3 (CMA3) can be used to show protamine deficiency in sperm chromatin. Fixed chromatin of mature mouse spermatozoa showed high fluorescence after treatment with ethidium bromide (EB), but was completely unstained after treatment with CMA3. The same chromatin was found to be highly resistant to in situ nick-translation. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
144
1
10

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(164 citation statements)
references
References 31 publications
9
144
1
10
Order By: Relevance
“…In this connection, it must be remembered that several studies have demonstrated that a variable but consistent fraction of human spermatozoa exhibits abnormalities in chromatin structure, not always detected using classical parameters of evaluation (12)(13)(14)(15)(16)(17)(18)(33)(34)(35). Moreover the existence of a close relationship between chromatin and DNA structural abnormalities and male infertility has been well pointed out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this connection, it must be remembered that several studies have demonstrated that a variable but consistent fraction of human spermatozoa exhibits abnormalities in chromatin structure, not always detected using classical parameters of evaluation (12)(13)(14)(15)(16)(17)(18)(33)(34)(35). Moreover the existence of a close relationship between chromatin and DNA structural abnormalities and male infertility has been well pointed out.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, a number of studies have shown that variable but consistent fractions of human spermatozoa not always detectable on the basis of classic morphological parameters, contain serious chromatin structural abnormalities and DNA strand breaks (12)(13)(14)(15)(16)(17)(18). The existence of an association between sperm chromatin malformation and male infertility has been repeatedly observed in humans and structural chromatin abnormalities have been found to exert negative effects both on the percentage of fertilization and on embryonic development (17,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For staining, 20 μl of CMA3 stain was pipetted onto the slide, covered with glass coverslip (22×22 mm) and incubated at room temperature for 20 min. Slides were rinsed in PBS and mounted with buffered glycerol [17]. Sperm head staining pattern was observed under fluorescent microscope with an oil immersion objective(Zeiss microscope, Axioskope 2 plus; Carl Zeiss, Gottingen, Germany) at 63 x magnification with appropriate filters (460-470 nm).…”
Section: Chromomycin A3 (Cma3) Stainingmentioning
confidence: 99%
“…Our flow cytometry-based chromomycin A3 (CMA3) quantification was adapted from the slide-based method (47). The CMA3 was dissolved in McIlvaine's buffer (17 mL of 0.1 mol/L citric acid mixed with 83 mL of 0.2 mol/L Na 2 HPO 4 and 10 mmol/L MgCl 2 , pH 7.0) to a concentration of 0.25 mg/mL.…”
Section: Chromomycin A3 Stainingmentioning
confidence: 99%